Qualidade de vida de mães de indivíduos com transtorno do espectro autista no envelhecimento - Piovesan, Josieli (2014)
In recent years, there has been a significant increase in the diagnosis of Autism Spectrum Disorder (ASD), which causes an increase of mothers involved in care. Therefore, the present dissertation aimed to investigate the Quality of Life (QL) of mothers of individuals with ASD in aging. The paper is organized into two sections: scientific production I and II. The first aimed to investigate the QL and the presence of depressive symptoms in mothers of individuals with ASD. The study included 40 women aged from 28 to 72 years, average 45.5 years old, married, living mostly in urban areas, with levels of education and middle-low income; mothers of individuals with ASD aged between 10 and 40 years, average age 19 years with cognitive impairment visitors specialized care institutions and / or special education schools, three institutions located in the northwestern region of Rio Grande do Sul and three in western Santa Catarina. In the study, cross-sectional, they were used as tools to characterize the sociodemographic and health of mothers and child with ASD questionnaire, the Quality of Life (WHOQOL-Bref), the Beck Depression Inventory (BDI II) Depression Scale Baptist Adult Version (EBADEP a) Inventory and Beck Hopelessness (BHS). Associations between numerical variables were assessed using the Spearman correlation coefficient, the tests were considered significant with a probability value <0.05. The scientific production II aimed to investigate the use of the internet as support to mothers of individuals with ASD tool. Instruments were used for collecting sociodemographic questionnaire and characterization of maternal health and the WHOQOL-Bref. The results indicated no relationship between the age factor and child QL and depressive symptoms in mothers. Internet use also showed no correlation with QL, although the participants consider this feature as important in the search for information and social interaction. There was a strong significant inverse correlation between quality of life and depressive symptoms. The environmental domain assessed by the WHOQOL-Bref showed moderate significant correlation with equities. Moreover, the income and education variables were significantly higher among mothers who use the internet. The results show the internet as an alternative support and knowledge to mothers. Thus, it is suggested to further study both with regard to QL and the presence of depressive symptoms on the use of the Internet as a tool support for these mothers